Perspectives juridiques sur le passé colonial belge, entre déni et justice - Marie-Sophie de Clippele (Criminocorpus)
The Belgian colonial past is re-emerging in public debate, from parliamentary circles to courtrooms, not to mention places of action and militancy within civil society. There is a strong demand for a work of justice and more broadly of reparation in the face of this past. However, the law seems ill-equipped to respond to these challenges. It can give the impression of a denial of justice in the face of particularly odious acts of the past, as it would be too late to judge them. Civil and criminal prescription appears merciless in this regard, particularly in the case of cultural objects. Although necessary to ensure a form of legal security and social stability, criminal prescription does however have some exceptions, mainly for heinous crimes. But a recent case involving crimes against humanity during Belgian colonization seems to undermine this path for the moment. Furthermore, other forms of justice than the classical routes of civil or criminal law are being explored by the Belgian legislator, within the paradigm of transitional justice. Thus, the Special Commission for the colonial past, established within the Federal Parliament, would work towards truth and reconciliation, but recently ended in failure. Moreover, the law of July 3, 2022 on the restitution of colonial collections opens new perspectives of reparation. It must be noted, however, that these various mechanisms, still to become more concrete, cannot really satisfy the reparation demands of the victims of acts perpetrated during Belgian colonisation.